EFEKTIVITAS KEPEMIMPINAN PEREMPUAN DALAM MENINGKATKAN KUALITAS PENDIDIKAN PESANTREN MELALUI SUPERVISI AKADEMIK - Daniati, S.; Patimah, Siti; Warisno, A.; Arafah, A. Latief Arung (FIKRAH, 2025)
Concern for women's resources with the role of the caliphate on this earth with reference to religious values and the noble values of the nation's culture, needs to be synergized in the context of the public and domestic dimensions at the same time. The public dimension concerns the role of women in the fields of science and technology, economy, employment, politics and national security. To find out how women lead, research was carried out using the method This qualitative research is descriptive and explanatory which provides a description of complex situations, and the direction for further research also provides an explanatory or explanation of the relationship between events and meanings, especially according to the perception of participants. After conducting research, it was concluded that women's leadership at the Putri Ishlahul Ummah Islamic Boarding School in Tasikmalaya City has proven its effectiveness in improving the quality of education through academic supervision. With an empathetic, communicative, and empowerment-focused approach, this leadership has succeeded in creating an inclusive and progressive educational environment. However, to maintain the sustainability of this program, support from various parties, including the government, the community, and religious organizations is needed. Thus, pesantren can continue to develop as an educational institution that is relevant to the challenges of the times.